AN IMPROVED TOPOLOGY OF SINGLE-PHASE LINEAR PERMANENT MAGNET GENERATOR FOR WAVE ENERGY CONVERSION SYSTEM - MEMON, AAMIR HUSSAIN (2019)
Ocean wave energy is one of the leading energy sources and contains enormous amount of power that can be harnessed in a variety of methods. This research aims to develop a simple, lightweight and high efficiency linear generator for point absorber wave energy conversion system